Riots and mutinys. Social conflict in the Guaraní towns of the missionary region (1768-1799) - Juan Luis Hernández (Memoria Americana. Cuadernos de Etnohistoria, 2000)
This article deals with social conflict in Guaraní towns in the Misiones area during the last three decades of the XVIII century. In other words from the Jesuits expulsion in 1768 until the beginning of Viceroy Avilés term in 1799 durin which the towns regime was modified. Different ways of community protests will be analyzed drawing the historical contex that produced them observing the actors behavior -elite and indigenous multitudes, administrators, public officuials. Going beyond the habitual image of the Guaraníes as indifferent and submissive people, a complex historical reconstruction will be appreciated, stressing the struggle of a group in order to overcome the injustices they were submitted to.